Exploring the levels of variation, inequality and use of physical activity intervention referrals in England primary care from 2017–2020: a retrospective cohort study - Uy Hoang; Harshana Liyanage; Simon de Lusignan; John Williams; Filipa Ferreira; Ivelina Yonova; Julian Sherlock; Anant Jani; Dylan McGagh; Cecilia Okusi (BMJ Open)
Objectives In this study, we explore the use of physical activity intervention referrals in primary care in England and compare their use with the rate of cardiovascular disease (CVD) risk factors in England from 2017 to 2020. We also explore variation and inequalities in referrals to these interventions in England across the study period.Design Retrospective cohort study.Setting England primary care via the Royal College of General Practitioners Research Surveillance Centre.Participants The Royal College of General Practitioners Research Surveillance Centre, a sentinel network across England covering a population of over 15 000 000 registered patients, was used for data analyses covering the 2017–2020 financial years and including patients with long-term conditions indicating CVD risk factors.Outcome measures An existing ontology of primary care codes was used to capture physical activity interventions and a new ontology was designed to cover long-term conditions indicating CVD risk factors. Single factor analysis of variance, paired samples t-test and two-tailed, one proportion z-tests were used to determine the significance of our findings.Results We observed statistically significant variation in physical activity intervention referrals for people with CVD risk factors from different ethnic groups and age groups across different regions of England as well as a marked decrease during the COVID-19 pandemic. Interestingly, a significant difference was not seen for different socioeconomic groups or sexes. Across all attributes and time periods (with the exception of the 18–39 group, 2017–2019), we observed a statistically significant underuse of physical activity intervention referrals.Conclusions Our findings identified statistically significant variation and underuse of physical activity referrals in primary care in England for individuals at risk of CVD for different population subgroups, especially different ethnicities and age groups, across different regions of England and across time, with the COVID-19 pandemic exerting a significant negative impact on referral rates.